Research on technical approach for train braking speed limits based on locomotive automatic operation system - CAI Yonghui; ZHOU Wenwei (机车电传动)
The deceleration and stopping process of freight trains on downslope sections through air braking, may encounter low converted pressure values of the brake shoes per 100 tons of train weight. Failure to timely reduce train speeds below the braking limit and control train operation within the speed limit could potentially result in hazards such as overspeeding and overrunning. To address this challenge, a calculation method for train braking speed limits was designed, tailored for the locomotive automatic operation system. Based on the train braking speed limit curve, functions for train operation curve planning, driving control, and safety protection were developed, which ensured the operational safety of trains in the automatic operation mode. Results from practical applications show the effectiveness of the proposed approach in improving the efficiency of train operation compared with manual driving.